A low-cost, environment-friendly and solvent-free route for synthesis of AgBr nanoparticles. (June 2015) - Shahsavani, Ensieh; Khalaji, Aliakbar Dehno; Feizi, Nourollah; Das, Debasis; Matalobos, Jesus Sanmartin; Kučeráková, Monika; Dušek, Michal
Highlights: AgBr nanoparticles <20 nm were synthesized from AgN03 and a ligand Brcats. Brcatsc was prepared from alpha-bromocinnamaldehyde and thiosemicarbazode in ethanol. The crystal structure of Brcatsc was determined by single crystal X-ray diffraction. The size and morphology of AgBr nanoparticles can be controlled by several methods. Abstract: We report on the synthesis of AgBr nanoparticles average size below 20 nm by from AgNO3 and a thiosemicarbazone ligand, Brcatsc [Brcatsc = 2-bromo-3-phenylpropenalthiosemicarbazone]. Brcatsc was prepared by reacting α-bromocinnam-aldehyde and thiosemicarbazide (1:1, molar ratio) in hot ethanol characterized by elemental analyses (CHN), FT-IR, 1 H NMR spectroscopy and single crystal X-ray diffraction. AgBr nanoparticles were prepared by heating the mixture of AgNO3 and Brcatsc at 600 °C for 3 h under aerobic condition, and characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The XRD pattern clearly indicates the formation of AgBr nanoparticles while SEM and TEM results reveal their uniformity and purity.